2007
DOI: 10.1007/s10592-007-9422-z
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris)

Abstract: The sea otter has experienced a dramatic population decline caused by intense human harvesting, followed by a century of recovery including relocation efforts to reestablish the species across its former range in the eastern Pacific. Although the otter was historically present along the coast in Oregon, there are currently no populations in this region and reintroduction efforts have failed. We examined the mtDNA genotypes of 16 pre-harvest otter samples from two Oregon locations in an attempt to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
0
27
2
Order By: Relevance
“…In the case of the sea otter (Enhydra lutris), genetic data from microsatellites show dramatic losses in heterozygosity and allelic diversity following the fur trade; however, otter population structure seems consistent through time [27]. Interestingly, mtDNA of archaeological sea otters from Oregon showed that they were more closely related to the least genetically diverse otter population from California, rather than Alaska, the source population for the unsuccessful Oregon otter reintroduction [28]. Studies such as these demonstrate the value of archaeological samples for identifying appropriate source populations for reintroductions.…”
Section: Demographic and Distributional Shiftsmentioning
confidence: 99%
“…In the case of the sea otter (Enhydra lutris), genetic data from microsatellites show dramatic losses in heterozygosity and allelic diversity following the fur trade; however, otter population structure seems consistent through time [27]. Interestingly, mtDNA of archaeological sea otters from Oregon showed that they were more closely related to the least genetically diverse otter population from California, rather than Alaska, the source population for the unsuccessful Oregon otter reintroduction [28]. Studies such as these demonstrate the value of archaeological samples for identifying appropriate source populations for reintroductions.…”
Section: Demographic and Distributional Shiftsmentioning
confidence: 99%
“…Stringent measures employed in successful ancient/ historical DNA projects (Valentine et al 2008, McMenamin & Hadly 2012 were instigated to eliminate contamination risks. All DNA extractions, including those from teeth, took place in laboratories free of contemporary shark material, and separate tools were designated for use on historical tissue and cleaned with 25% sodium hypochlorite solution between samples.…”
Section: Contamination Controlsmentioning
confidence: 99%
“…Pacific Otters-As discussed by Valentine et al (2008), extensive hunting during the eighteenth and nineteenth centuries led to drastic reductions in sea otter (Enhydra lutris) populations in the eastern Pacific Ocean, particularly in Oregon, where they were extirpated. Attempted reintroductions of sea otters to this region have been largely unsuccessful despite more fruitful results in areas to the north, and recent research has provided several important clues as to why the Oregon reintroduction failed.…”
Section: Mountain Goats In Washingtonmentioning
confidence: 99%
“…Studies of morphological (Wilson et al 1991) and genetic (Valentine et al 2008) variation suggest that there are several distinct genotypes associated with three different subspecies of sea otter: the common sea otter (E. l. lutris), the southern sea otter (E. l. nereis), and the northern sea otter (E. l. kenyoni). In the case of Oregon reintroduction efforts, a population of northern sea otters was transplanted from Alaska.…”
Section: Mountain Goats In Washingtonmentioning
confidence: 99%
See 1 more Smart Citation